2003
DOI: 10.1071/bt02110
|View full text |Cite
|
Sign up to set email alerts
|

Responses of freshwater biota to rising salinity levels and implications for saline water management: a review

Abstract: All of the plants and animals that make up freshwater aquatic communities are affected by salinity. Many taxa possess morphological, physiological and life-history characteristics that provide some capacity for tolerance, acclimatisation or avoidance. These characteristics impart a level of resilience to freshwater communities.To maintain biodiversity in aquatic systems it is important to manage the rate, timing, pattern, frequency and duration of increases in salinity in terms of lethal and sublethal effects,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(143 citation statements)
references
References 52 publications
(73 reference statements)
4
131
1
Order By: Relevance
“…Yet, adaptive behaviour, such as the avoidance of saline water bodies, may assist the persistence of aquatic invertebrates that are halosensitive and influence Significant results are shown in bold population dynamics more widely (Spencer et al, 2002;James et al, 2003;Neilsen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, adaptive behaviour, such as the avoidance of saline water bodies, may assist the persistence of aquatic invertebrates that are halosensitive and influence Significant results are shown in bold population dynamics more widely (Spencer et al, 2002;James et al, 2003;Neilsen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The influence of abiotic factors on colonisation behaviour may strongly influence assemblage structure and population dynamics (James et al, 2003;Silberbush et al, 2005). Analysis of assemblages revealed that salinity is a determinant of assemblages that colonise the mesocosms, broadly influencing selective behaviour.…”
Section: Influence Of Salinity On Insect Assemblagesmentioning
confidence: 99%
See 1 more Smart Citation
“…I expect this is because it is the only paper on the topic. In contrast, in the review undertaken in 2002 of the salinity responses of the Australian freshwater biota (Bailey et al 2002), we had 169 entries for the salinity tolerance of angiosperms alone (see also the review articles published around this time by Hart et al 2003, James et al 2003and Nielsen et al 2003, all of which dealt largely with the biota of inland, not coastal, systems).…”
Section: Research Investment and Implications For Knowledge Generationmentioning
confidence: 99%
“…; James et al, 2003). Freshwater species may sometimes be replaced by more salt-tolerant species such as three-spined stickleback (Gasterosteus aculeatus), nine-spined stickleback (Pungitius pungitius), mosquito fish (Gambusia holbrooki) or sand smelt (Atherina presbyter) (Jeppesen et al, 1994;Brucet et al, 2010).…”
Section: Effects Of Changes In Salinity/conductivitymentioning
confidence: 99%